CHARACTERIZATION OF LACTIC ACID BACTERIA FROM CINCALUK BASEDON16S rRNA SEQUENCE - Putri Ayu; Nursyirwani Nursyirwani; Feliatra Feliatra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Lactic acid bacteria (LAB) is a groupof bacteria frequently used as probiotic in aquaculture because of its beneficial effects on health, pathogenic bacteria prevention and increase of fish growth. LAB could be found in fermented fish products such as Cincaluk that is produced by people in Tembilahan and Bengkalis of Riau Province. The purpose of this research was to characterize LAB isolated from Cincaluk Tembilahan and Bengkalis genetically. This research was conducted from February until May 2018. Bacterial isolates were identified based on morphology, biochemical characters and 16S rRNA sequence. 24 isolates found were round, creamy white, Gram positive, did not produce indole, produced catalase, non motil, used citrate, did Methyl Red, produced H2S and gas, glucose, sucrose and lactose were fermented. Based on 16S rRNA sequence. Five of six isolates selected were identified as Lactobacillus plantarum (97-100% similarites) and one isolate was Bacillus cereus (94%) Keyword:Characteristic, Lactid Acid Bacteria, Cincaluk, Genetic,16S rRNA sequence